Extended Swan‐Neck Catheter With Upper Abdominal Exit‐Site Reduces Peritoneal Dialysis‐Related Infections. Issue 2 (14th January 2016) - Eriguchi, Masahiro; Tsuruya, Kazuhiko; Yoshida, Hisako; Haruyama, Naoki; Tanaka, Shigeru; Tsuchimoto, Akihiro; Fujisaki, Kiichiro; Torisu, Kumiko; Masutani, Kosuke; Kitazono, Takanari
Abstract: Extended catheters with an upper abdominal exit‐site (UAE) are reportedly associated with a lower incidence of peritoneal dialysis (PD)‐related infections. However, little information about the optimal peritoneal catheter configuration for UAE is available. In this nonrandomized multicenter trial, 147 consecutive cases of a UAE involving either a conventional straight (CS; 80 cases) or extended swan‐neck catheter (SN; 67 cases) were analyzed to compare exit‐site and tunnel infections (ESTI), peritonitis, and catheter survival. The ESTI‐free and catheter survival rates were significantly lower in the SN than in the CS group ( P <0.01). However, the peritonitis‐free survival rate was not different ( P = 0.26). In terms of analyses for infection rates, fewer episodes of ESTI (1.284 vs 0.608 episodes/patient‐year; P <0.01) and peritonitis (0.345 vs 0.152 episodes/patient‐year; P = 0.06) were observed in the SN than CS group. Recurrence analyses showed that the mean number of cumulative episodes of ESTI and peritonitis between two groups were significantly different.